Reexpansion Pulmonary Edema - Yasemin Işık; İsmail Katı; Onur Palabıyık; Uğur Göktaş (Galenos Yayinevi, 2011)
Reexpansion pulmonary edema is a rare but life threating complication which is occurring during the treatment of lung collapse secondary to pleural effusion, pneumothorax or atelectasis. We presented a 68 year-old case with hypertension, heart failure, cerebrovascular disease and diabetes mellitus who had developed reexpansion pulmonary edema three hours after the application of unilateral thoracentesis (Journal of the Turkish Society of Intensive Care 2011; 9: 26-9)